2021
DOI: 10.1155/2021/6617437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subsurface Drip Irrigation on Water Consumption and Yields of Alfalfa under Different Water and Fertilizer Conditions

Abstract: A field experiment was conducted for the purpose of examining the effects of different combinations of water and fertilizer applications on the water consumption and yields of alfalfa under subsurface drip irrigation (SDI). The results showed that the jointing and branching stages were the key stages for alfalfa water requirement. The water consumption had varied greatly (from 130 to 170 mm) during the growth period of each alfalfa crop. The water consumption during the whole growth period was approximately 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…Soil parameters affect plant growth and soil microorganisms. In the present study, TA and FA reduced soil moisture content, soil electrical conductivity, soil available phosphorus, and soil total phosphorus at the 15-30 cm soil depth (Huang et al, 2018;Cao et al, 2021), which is consistent with our finding that TA and FA reduced soil moisture content. Meanwhile, alfalfa increased pH value and reduced soil electrical conductivity.…”
Section: Discussionsupporting
confidence: 93%
“…Soil parameters affect plant growth and soil microorganisms. In the present study, TA and FA reduced soil moisture content, soil electrical conductivity, soil available phosphorus, and soil total phosphorus at the 15-30 cm soil depth (Huang et al, 2018;Cao et al, 2021), which is consistent with our finding that TA and FA reduced soil moisture content. Meanwhile, alfalfa increased pH value and reduced soil electrical conductivity.…”
Section: Discussionsupporting
confidence: 93%
“…This resulted in a change in the SWS for S3 that was significantly higher than that of the other salinity levels (Table 2). The increase in amount of irrigation aggravated this phenomenon (Table 2), which is consistent with the findings of previous studies [9,33]. Moreover, the water consumption and aboveground biomass for S2W1 were higher than those of S0W1 in both years, with an average increase of 6.49% and 2.17%, respectively (Tables 1 and 2).…”
Section: Effects Of Water and Salt Stress On The Growth And Water Con...supporting
confidence: 90%
“…Alfalfa, as a forage crop with high water consumption, varies greatly in its consumption of water (130-170 mm) during the growth period. The jointing and branching stages are the key periods when alfalfa requires water [33]. The yield is most obviously affected by water stress during these stages [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that SSDI can decrease evapotranspiration and improve water production. The subsurface drip irrigation method has been used in the irrigation of sorghum, alfalfa, and vegetables [10,11]. For tomato cultivation, Incrocci et al (2006) found that subirrigation can be a tool to reduce water consumption.…”
Section: Introductionmentioning
confidence: 99%